Larvicidal efficacy and morphological abnormalities induced by plant essential oils against housefly (Musca domestica L.) - Passara, H.; Sittichok, S.; Moungthipmalai, T.; Laosinwattana, C.; Thongsaiklaing, M.; Murata, K.; Soonwera, M. (My University, 2026)
The results showed that the lowest complete pupation rate was 43.67%, indicating a significant inhibition of normal metamorphosis. Additionally, 56.33% of third-instar larvae were classified as malformed larvae (ML), dying before pupation and exhibiting severe morphological and physiological abnormalities. These findings suggest that the star anise nanoemulsion interferes with key developmental pathways, preventing larvae from reaching the pupal stage. Due to its high effectiveness and plant-based origin, this nanoformulation offers a promising, environmentally friendly alternative to conventional chemical insecticides. It has potential for further development into a natural larvicidal agent for use in integrated pest management (IPM) strategies targeting housefly populations. Future research should explore the underlying mechanisms of action and assess the efficacy and safety of this nanoemulsion under real-world conditions to support its application in sustainable vector control.
Keywords: Botanical insecticide; Housefly; Larvicidal; Morphological abnormalities; Plant essential oils